PERSEPSI SISWA TERHADAP KOMPETENSI SOSIAL GURU DI SMA NEGERI 1 PAYAKUMBUH - Putri Utami; Nellitawati Nellitawati; Hadiyanto Hadiyanto; Merika Setiawati (STKIP Pesisir Selatan, 2026)
Objective Teachers' social competence plays an important role in creating harmonious relationships and supporting the success of the learning process. However, several issues related to teacher-student communication, objectivity in treating students, and politeness in interactions during the learning process are still observed. This study aimed to describe students' perceptions of teachers' social competence at SMA Negeri 1 Payakumbuh, covering communication skills, objective behavior, and polite social interaction. This study employed a descriptive quantitative approach. The population consisted of 866 tenth- and eleventh-grade students, with a sample of 104 students selected using the Proportionate Stratified Random Sampling technique. Data were collected through a Likert-scale questionnaire that had met the validity and reliability requirements and were analyzed using the mean score technique. The results revealed that students' perceptions of teachers' social competence were categorized as good, with an average score of 3.08. Communication skills obtained an average score of 3.26 (very good), objective behavior obtained 3.09 (good), and polite social interaction obtained 2.88 (good). These findings indicate that teachers' social competence has been implemented well; however, the aspect of polite social interaction still requires improvement. The implication of this study highlights the importance of strengthening teachers' social competence to foster more effective interactions.